Caste, Land and Labor Market Imperfections, and Land Productivity in Rural Nepal - Jeetendra P. Aryal; Stein T. Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2011)
This paper provides new evidence on the caste-related land productivity differential and its explanations in rural Nepal using household plot panel data. Low-caste households are found to have significantly higher land productivity on their owner-operated plots as compared to high-caste households. A comparison between the rented in land of low-caste and the owneroperated land of high-caste households showed that the former has significantly higher land productivity. No significant Marshallian inefficiency was found in the case of low-caste tenant households. Land productivity differences are explained by transaction costs in the labor market and caste discrimination rather than the disincentive effect of sharecropping
Keywords: Q12; Q15; 330; land productivity; high-caste landlords; low-caste tenants; transaction costs; sharecropping; market imperfections; Nepal